Effect of blood pressure reduction on cardiovascular outcomes in patients with different baseline cardiovascular risk: systematic review and meta-analysis of randomized trials. (3rd October 2022) - Manta, E; Thomopoulos, C; Drogkaris, S; Dimitriadis, K; Polyzos, D; Kariori, M; Filippou, C; Siafi, E; Tatakis, F; Konstantinidis, D; Tsioufis, K
Abstract: Background/Introduction: Blood pressure (BP) lowering is accompanied by a reduction on cardiovascular (CV) outcomes and death in hypertensive patients. There is no data on the effect of lowering BP in patients stratified according to their baseline CV risk as indicated by SCORE 2. Purpose: The aim of this meta-analysis was to demonstrate the impact of BP-lowering treatment on the occurrence of CV events in these previously reported patients. Methods: A systematic review in electronic databases (Pubmed and CENTRAL, years: 1966 to 9/2021) was conducted to identify randomized trials that study the effect of BP-lowering treatment against placebo or less aggressive BP reduction on 6 fatal or non-fatal CV outcomes and all-cause death. Selected studies reported outcomes in patients without a history of previous CV disease. In each study, baseline cardiovascular risk was estimated using SCORE-2. Risk ratios (RR) were calculated together with their 95% confidence interval (CI) under the random-effects model. Results: The analysis was composed of 54 studies, of which 12 trials included patients with low-to-moderate CV risk, (n=21, 192 patients), 13 trials with high CV risk patients (n=66, 886) and 29 trials with very high CV risk patients (n=79, 061). For a standard SBP/DBP reduction of 10/5 mmHg, the relative risk of the combined outcome of major CV events (i.e., myocardial infarction, stroke, and heart failure) was decreased by 27% (95% CI, 22–35%) in the category of very high-risk patients. This reduction was significantly greater (p=0.02) compared to high-risk trials (0.90 [95% CI, 0.77–1.04]). CV death showed a significant reduction in the high-risk group of patients compared to the low-moderate risk group (p=0.005), as well as in the very high-risk group compared to the low-moderate risk group (p=0.001). The same pattern was observed for all-cause death in the very high-risk group compared to the high-risk group (p=0.045). Conclusions: With the present meta-analysis, we observed that the greatest benefit from BP lowering in primary prevention in the occurrence of CV events and mortality is observed in patients at higher baseline cardiovascular risk, as calculated by the SCORE-2. Funding Acknowledgement: Type of funding sources: None.